Are Racial Disparities in Cesarean Due to Differences in Labor Induction Management? - Hamm, Rebecca F.; McCoy, Jennifer A.; Clark, Rebecca R.S.; Parry, Samuel; Levine, Lisa D. (American Journal of Perinatology, 2024)
Objective While there are known racial disparities in cesarean delivery (CD) rates, the exact etiologies for these disparities are multifaceted. We aimed to determine if differences in induction of labor (IOL) management contribute to these disparities.Study Design This retrospective cohort study evaluated all nulliparous patients with an unfavorable cervix and intact membranes who underwent IOL of a term, singleton gestation at a single institution from October 1, 2018, to September 30, 2020. IOL management was at clinician discretion. Patients were classified as Black, Indigenous, and People of Color (BIPOC) or White based on self-report. Overall rates of CD were compared for BIPOC versus White race. Chart review then evaluated various IOL management strategies as possible contributors to differences in CD by race.Results Of 1,261 eligible patients, 915 (72.6%) identified as BIPOC and 346 (27.4%) as White. BIPOC patients were more likely to be younger (26 years interquartile range (IQR): [22–30] vs. 32 years IQR: [30–35], p < 0.001) and publicly insured (59.1 vs. 9.9%, p < 0.001). Indication for IOL and modified Bishop score also differed by race (p < 0.001; p = 0.006). There was 40% increased risk of CD for BIPOC patients, even when controlling for confounders (30.7 vs. 21.7%, p = 0.001; adjusted relative risk (aRR) = 1.41, 95% confidence interval (CI): [1.06–1.86]). Despite this difference in CD, there were no identifiable differences in IOL management prior to decision for CD by race. Specifically, there were no differences in choice of cervical ripening agent, cervical dilation at or time to amniotomy, use and maximum dose of oxytocin, or dilation at CD. However, BIPOC patients were more likely to undergo CD for fetal indications and failed IOL.Conclusion BIPOC nulliparas are 40% more likely to undergo CD during IOL than White patients within our institution. These data suggest that the disparity is not explained by differences in IOL management prior to cesarean, indicating that biases outside of induction management may be important to target to reduce CD disparities.Key Points
Keywords: racial disparities; labor induction; cesarean delivery; health equity; implicit bias